Why are bleeding trauma patients still dying? Towards a systems hypothesis of trauma - Dobson, Geoffrey P.; Morris, Jodie L.; Letson, Hayley L. (Frontiers in Physiology, 2022)
Over the years, many explanations have been put forward to explain early and late deaths following hemorrhagic trauma. Most include single-event, sequential contributions from sympathetic hyperactivity, endotheliopathy, trauma-induced coagulopathy (TIC), hyperinflammation, immune dysfunction, ATP deficit and multiple organ failure (MOF). We view early and late deaths as a systems failure, not as a series of manifestations that occur over time. The traditional approach appears to be a by-product of last century’s highly reductionist, single-nodal thinking, which also extends to patient management, drug treatment and drug design. Current practices appear to focus more on alleviating symptoms rather than addressing the underlying problem. In this review, we discuss the importance of the system, and focus on the brain’s “privilege” status to control secondary injury processes. Loss of status from blood brain barrier damage may be responsible for poor outcomes. We present a unified Systems Hypothesis Of Trauma (SHOT) which involves: 1) CNS-cardiovascular coupling, 2) Endothelial-glycocalyx health, and 3) Mitochondrial integrity. If central control of cardiovascular coupling is maintained, we hypothesize that the endothelium will be protected, mitochondrial energetics will be maintained, and immune dysregulation, inflammation, TIC and MOF will be minimized. Another overlooked contributor to early and late deaths following hemorrhagic trauma is from the trauma of emergent surgery itself. This adds further stress to central control of secondary injury processes. New point-of-care drug therapies are required to switch the body’s genomic and proteomic programs from an injury phenotype to a survival phenotype. Currently, no drug therapy exists that targets the whole system following major trauma.